2006
DOI: 10.1071/ea04245
|View full text |Cite
|
Sign up to set email alerts
|

Response of tropical turfgrasses to recycled water in southern Queensland

Abstract: The effects of recycled water (effluent) on 8 tropical grasses growing in 100-L bags of sand were studied in Murrumba Downs, just north of Brisbane in southern Queensland (27.4°S, 153.1°E). The species used were: Axonopus compressus (broad-leaf carpetgrass), Cynodon dactylon (bermudagrass ‘Winter Green’) and C. dactylon × C. transvaalensis hybrid (‘Tifgreen’), Digitaria didactyla (Queensland blue couch), Paspalum notatum (bahiagrass ‘38824’), Stenotaphrum secundatum (buffalograss ‘Palmetto’), Eremochloa ophiur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this study, we hypothesized that irrigation using TSE as a partial source of N associated with N regular-fertilizer may affect DM production and N concentration in the shoots and the economic feasibility. Menzel and Broomhall (2006) identified an increase of 4% on DM for bermudagrass irrigated with TSE in comparison to irrigation with potable water. These authors reported a 40% decrease in N leaf concentration in plants irrigated with TSE between May and August.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we hypothesized that irrigation using TSE as a partial source of N associated with N regular-fertilizer may affect DM production and N concentration in the shoots and the economic feasibility. Menzel and Broomhall (2006) identified an increase of 4% on DM for bermudagrass irrigated with TSE in comparison to irrigation with potable water. These authors reported a 40% decrease in N leaf concentration in plants irrigated with TSE between May and August.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1960 and 2010 the average U.S. farm price of a ton of urea fertilizer (44-46% of N) increased from US$ 82 to US$ 448 (USDA, 2010). Menzel and Broomhall (2006) concluded that TSE costs 50% of the costs of potable water (PW), thus enabling savings of AU$ 8000 ha −1 year −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Soil from Golf Course A fairways had greater K concentration than that of Golf Course B in 2010, 2012, and 2013, or 3, 5, and 6 yr after effluent water irrigation started on Golf Course A. These differences could be due to the amount of K in effluent water as Menzel and Broomhall (2006) have indicated.…”
Section: Resultsmentioning
confidence: 94%
“…Soil Na concentration increased almost 5.5 times since the start of using effluent water, and the value (156 kg ha −1 ) was in the moderate risk range (>210 is in high risk) [23]. A study Arid Environments and Sustainability done in 2005 found that effluent water provided enough K, Ca, and Mg for plants [24]. The authors suggested that soil with excessive amounts of K could lead to base saturation imbalance, and highly soluble salts tie up other elements such as B, Ca, and Mg.…”
Section: Resultsmentioning
confidence: 99%